2021
DOI: 10.3390/en14227526
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Renewable Energy Consumption in the European Countries—The Bayesian Averaging Classical Estimates Approach

Abstract: The paper aims to identify the most likely factors that determine the demand for energy consumption from renewable sources (renewable energy consumption—REC) in European countries. Although in Europe, a high environmental awareness is omnipresent, countries differ in scope and share of REC due to historical energetic policies and dependencies, investments into renewable and traditional energetic sectors, R&D development, structural changes required by energetic policy change, and many other factors. The st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, by combing through the literature, the authors found that most of them used different types of models when reviewing the determinants of the international investment-renewable energy consumption-environment quality nexus, and often ignored the institutional effect on this nexus. Recently, a few studies have just begun to involve the role of institutional quality in this nexus [99,100], but more research is still needed to further explore the specific mechanism of institutional quality in different regions to further enrich the results in this field.…”
Section: The Mechanism Of Institutional Quality In the International ...mentioning
confidence: 99%
“…However, by combing through the literature, the authors found that most of them used different types of models when reviewing the determinants of the international investment-renewable energy consumption-environment quality nexus, and often ignored the institutional effect on this nexus. Recently, a few studies have just begun to involve the role of institutional quality in this nexus [99,100], but more research is still needed to further explore the specific mechanism of institutional quality in different regions to further enrich the results in this field.…”
Section: The Mechanism Of Institutional Quality In the International ...mentioning
confidence: 99%